2019
DOI: 10.1016/j.diabet.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Non-targeted metabolomic biomarkers and metabotypes of type 2 diabetes: A cross-sectional study of PREDIMED trial participants

Abstract: The multi-metabolite signature of T2D highlights the altered metabolic fingerprint associated mainly with amino-acid, carbohydrate and microbiota metabolism. Metabotypes identified in this patient population could be related to higher risk of long-term cardiovascular events and therefore require further studies. Metabolomics is a useful tool for elucidating the metabolic complexity and interindividual variation in T2D towards the development of stratified precision nutrition and medicine. Trial registration at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 40 publications
3
38
0
Order By: Relevance
“…The findings relating to the urea cycle metabolites was consistent with the results of a separate study which discovered that patients with T2DM had increased plasma levels of arginine, and decreased levels of ornithine [277]. Furthermore, metabolite profiling has revealed significant differences in the levels of certain urinary metabolites such as alanine, betaine, formic acid, and trigonelline, between diabetic and non-diabetic individuals [278]. Investigating the metabolic pathways that involve these metabolites may provide new insights into the pathophysiology of diabetes and the involvement of these metabolites.…”
Section: Metabolite Profilingsupporting
confidence: 82%
“…The findings relating to the urea cycle metabolites was consistent with the results of a separate study which discovered that patients with T2DM had increased plasma levels of arginine, and decreased levels of ornithine [277]. Furthermore, metabolite profiling has revealed significant differences in the levels of certain urinary metabolites such as alanine, betaine, formic acid, and trigonelline, between diabetic and non-diabetic individuals [278]. Investigating the metabolic pathways that involve these metabolites may provide new insights into the pathophysiology of diabetes and the involvement of these metabolites.…”
Section: Metabolite Profilingsupporting
confidence: 82%
“…The recent study reported several alterations of CHD and DB in metabolic pathway, including cAMP signaling pathway (28) , glycolysis/gluconeogenesis and pyruvate metabolism (29) , which keep consistent with our results (Fig. 1).…”
Section: Discussionsupporting
confidence: 93%
“…Type 1 diabetes risk is traditionally associated with autoimmunity, and lysophosphatidylcholine (18:0/0:0), BCAA, and glutamic acid are increased along with decreased glutamine and methionine levels before and after seroconversion with autoantibodies ( 23 , 24 ). Type 2 diabetes risk is associated with insulin resistance ( 25 ) and with elevated amino acids isoleucine, leucine, valine, tyrosine, and phenylalanine and decreased asparagine, glycine, and glutamine levels ( 25 , 26 ). Although this study only included participants with type 1 diabetes, given the contemporary changes in the phenotypes of patients with type 1 diabetes and that insulin resistance may be present in some participants, we stratified our cohorts based on highest daily insulin requirements and found no differences between these subgroups.…”
Section: Discussionmentioning
confidence: 99%